THE EFFECT OF GAMIFICATION LEARNING ON STUDENT MOTIVATION AND LEARNING OUTCOMES - Lukman Saleh; Budi Jaya Sugiarto (Consilium: Education and Counseling Journal, 2026)
The advancement of digital technology demands the implementation of innovative learning strategies to improve student motivation and learning outcomes. One strategy that has been widely developed is gamification learning, an approach that integrates game elements into learning activities. This study aims to examine the effect of gamification learning on the motivation and learning outcomes of students in the Digital Business Study Program in the Digital Marketing course. The study used a quantitative approach with a quasi-experimental method through a Pretest–Posttest Control Group Design. The sample size was 60 students, who were divided into an experimental group and a control group using a cluster random sampling technique. The research instruments included a learning motivation questionnaire compiled based on the ARCS Motivation Model and a learning outcome test. Data analysis was carried out using descriptive statistics, normality tests, homogeneity tests, paired mean difference tests, unpaired mean difference tests, and effect sizes (Cohen's d). The results showed that gamification learning had a positive and significant effect on student motivation and learning outcomes (p < 0.05). The experimental group experienced a higher increase in motivation and learning outcomes than the control group, with the effect size value being in the very large category. Therefore, gamification learning has proven effective in increasing student motivation and learning outcomes in Digital Marketing learning.